Analysis of the bond strength between conventional, putty or resin-modified calcium silicate cement and bulk fill composites - Ipek, I.; Eskibaglar, B. Karaagac; Yildiz, S.; Atas, O.; Unal, M. (Wiley, 2023)
Background: The aim of this study was to evaluate the shear bond strength of three different calcium silicate-based cements (CBCs) with two different bulk-fill composite resins (CRs). Methods: Plexiglas moulds with a diameter of 4 mm and a thickness of 2 mm were prepared (n = 60). The Biodentine, NeoPutty and MTA Cem LC samples were randomly divided into two subgroups containing 10 samples each. Surfaces of samples were air dried and Single Bond universal adhesive was applied. Cylindrical plastic capsules of 4 mm height and 2 mm inner diameter belonging to Filtek Bulk-fill and EverX Posterior CRs were centred on coating material and polymerized for 20 s. After shear bond strength (SBS) testing, all samples were examined by scanning electron microscopy (SEM) to identify failure patterns. Three samples, one from each group, were prepared to evaluate chemical composition of CBCs and examined with an energy dispersive X-ray spectroscopy for surface elemental analysis. Results: The values obtained from the tests were evaluated as statistically significant (P < 0.05). After SBS testing, the difference between all CBCs was statistically significant in both CRs. Conclusion: According to the findings in this study, it was concluded that MTA Cem LC had highest SBS values in both CRs. (c) 2023 Australian Dental Association.
Keywords: Bulk fill composite; failure type; sem; shear bond strength; tricalcium silicate